The Federal Reserve's implicit inflation target and macroeconomic dynamics: A SVAR analysis - Haroon Mumtaz; Konstantinos Theodoridis (Queen Mary University of London, School of Economics and Finance, 2017)
This paper identifies shocks to the Federal Reserve's inflation target as VAR innovations that make the largest contribution to future movements in long-horizon inflation expectations. The effectiveness of this scheme is documented via Monte-Carlo experiments. The estimated impulse responses indicate that a positive shock to the target is associated with a large increase in inflation, GDP growth and long-term interest rates. Target shocks are estimated to be a vital factor behind the increase in inflation during the pre-1980 period and are an important driver of the decline in long-term interest rates over the last two decades.
Keywords: C5; E1; E5; E6; 330; SVAR; DSGE model; inflation target